Uniform patchy and hollow rectangular platelet micelles from crystallizable polymer blends - Qiu, Huibin; Gao, Yang; Boott, Charlotte E.; Gould, Oliver E. C.; Harniman, Robert L.; Miles, Mervyn J.; Webb, Stephen E. D.; Winnik, Mitchell A.; Manners, Ian (Science (American Association for the Advancement of Science), 2016)
The preparation of colloidally stable, self-assembled materials with tailorable solid or hollow two-dimensional (2D) structures represents a major challenge. We describe the formation of uniform, monodisperse rectangular platelet micelles of controlled size by means of seeded-growth methods that involve the addition of blends of crystalline-coil block copolymers and the corresponding crystalline homopolymer to cylindrical micelle seeds. Sequential addition of different blends yields solid platelet block comicelles with concentric rectangular patches with distinct coronal chemistries. These complex nano-objects can be subject to spatially selective processing that allows their disassembly to form perforated platelets, such as well-defined hollow rectangular rings. The solid and hollow 2D micelles provide a tunable platform for further functionalization and potential for a variety of applications.